Current Status of Studying the Effectiveness of Ozone Therapy in Obstructive Diseases - Kuchkarova Shakhnoza (Global Scientific Publishing, 2023)
Ozone therapy has emerged as a compelling adjunctive intervention in the realm of obstructive diseases, specifically chronic obstructive pulmonary disease (COPD) and bronchial asthma. This review navigates through the current landscape of research, offering a detailed exploration of the therapeutic potential of ozone therapy in managing these intricate respiratory conditions. Highlighting the global health impact of obstructive diseases and the persisting challenges with conventional treatments, the introduction sets the context for considering alternative approaches, such as ozone therapy. The subsequent overview comprehensively examines ozone therapy, elucidating its diverse administration forms—ozonated water, gas, or oil—and delving into its fundamental mechanisms of action. By emphasizing its antiinflammatory, immunomodulatory, and antimicrobial properties, this section establishes a foundational understanding of how ozone therapy may address the multifaceted aspects of obstructive diseases. Moving into the intricacies of mechanisms of action, the article explores ozone therapy's impact on inflammatory pathways, immune responses, and tissue oxygenation. This section aims to provide a nuanced perspective on how ozone therapy may modulate the underlying factors contributing to obstructive respiratory conditions. The review critically analyzes key clinical studies and trials investigating ozone therapy's efficacy in COPD and bronchial asthma. Notable findings, including improved pulmonary function, reduced exacerbation rates, and enhanced quality of life, underscore the evolving evidence supporting ozone therapy's therapeutic role in obstructive diseases. Safety considerations are addressed in detail, exploring potential side effects and challenges associated with ozone therapy application in obstructive diseases. This thorough analysis informs the risk-benefit assessment, offering essential insights for clinicians and researchers contemplating the integration of ozone therapy into standard care. Recognizing current limitations, the article concludes by advocating for ongoing research efforts. The imperative for standardized protocols, larger sample sizes, and a deeper understanding of long-term effects underscores the necessity of well-designed clinical trials to establish ozone therapy's efficacy, safety, and sustained impact in the landscape of respiratory medicine.
Keywords: Ozone therapy; COPD